When Is WebAssembly Going to Get DOM Support? - Ehrenberg, Daniel (Communications of the ACM, 2025)
This article details the relationship between WebAssembly (Wasm), Document object models (DOMs) and JavaScript. The author shows an example workaround on how to overcome the limitations of Wasm by using glue code from JavaScript to connect to DOMs. Topics include Application Programming Interfaces (APIs), the World Wide Web Consortium Wasm Community Group, and Wasm Garbage collectors (GCs). Also presented are ways to reduce the overhead of programs that span the JavaScript/Wasm boundary.